Congenital atrophoderma of Pasini and Pierini. - Leite, I.; Guedes, R.; Luís, A.; Baptista, A.; Osório Ferreira, E. (European Journal of Pediatric Dermatology, 2011)
Atrophoderma of Pasini and Pierini (APP) is an uncommon localized dermal atrophy. We report the case of a congenital APP with a typical clinical picture and with changes of the elastic fibers on histopathology. To the best of our knowledge, this is the second case report of a congenital APP.